Clinical Study of Battlefield Acupuncture for Acute Pain and Edema Management in Distal Radius Fractures within an Emergency Setting - Feng, Li; Deng, Yufang (International Journal of Advanced AI Applications, 2026)
Distal radius fractures (DRF) are highly prevalent traumatic injuries often complicated by severe acute pain and prolonged edema, which hinder early functional recovery and increase healthcare burdens. This prospective, randomized controlled trial evaluated the efficacy of Battlefield Acupuncture (BFA) as an adjunct therapy for 64 patients with DRF during the acute edema phase. Participants were randomly assigned to either a BFA group (n=32), receiving auricular press needles at five specific points combined with standard manual reduction and splinting, or a Control group (n=32) receiving standard care alone. Results demonstrated that the BFA group achieved a superior analgesic effect, with Visual Analogue Scale (VAS) scores decreasing by over 50% within 72 hours post-intervention. Additionally, the BFA group showed significantly faster edema resolution, with the swelling index decreasing by 35.0 ± 4.2% within 72 hours (P=0.003), accompanied by a marked increase in serum β-endorphin levels (+42.3 ± 5.8 pg/mL, P<0.01) and reduced Substance P. No severe adverse events were observed, and the BFA group reported higher patient satisfaction and optimized medical resource utilization. In conclusion, BFA is a safe, effective, and economically feasible intervention that enhances acute symptom control and the early recovery trajectory of patients with distal radius fractures.